The role of metformin in the treatment of type 2 diabetes and obesity's - Vuković Mira H. (Srpsko lekarsko drustvo, 2016)
Topic: Mutual association and connection study between the obesity, visceral obesity, insulin desensitation (with the conesquential hyperinsulinemia), type 2 diabetes, dyslipoproteinemia and anthropometric characteristics of the patients with the metabolic syndrom are the subject of many epidemiological studies. However, it is noticed that there are certain disagreements and contradictions in defining the anthropometric and metabolic risk factors for the occurance of the cardiovascular, cerebrovascular and other vascular diseases, especially in population of the obese patients with type 2 diabetes. Topic position in medical public: Theoretically, metformin achieves a good glicoregulation preciselyinthe visceral obese patients. This is explained by a higher glucometabolic activity of the visceral adipose tissue in regard to the subcutenaus tissue. Further action: More efficient reduction of the visceral adipose tissue inpatients with achieved better glucoregulation, under the affection of the metformin is a result of its complex effect mechanism. Metformin plays a significant role in the reduction of the cardiovascular risk that comes from a higher visceral obesity, parallel to the achievement of the good glicoregulation in obese, type 2 diabetes patients.